110 Interim Federal Health Program (IFHP): Survey of Access & Utilization by Pediatric Health Care Providers. (29th October 2021) - Leps, Caroline; Monteiro, Jessica; Barozzino, Tony; Bowry, Ashna; Rashid, Meb; Sgro, Michael; Suleman, Shazeen
Abstract: Primary Subject area: Public Health and Preventive Medicine Background: Canada is currently facing an increasing number of refugees and refugee claimants, yet Canadian health professionals are underutilizing the system intended to provide these individuals with healthcare. The Interim Federal Health Program (IFHP) provides temporary healthcare coverage for those who are ineligible for provincial or territorial insurance, including resettled refugees and asylum seekers. Research suggests there are ongoing challenges around the program such as who is covered and what services are covered. Objectives: The objective of this study was to assess Canadian pediatricians' current understanding and utilization of the IFHP, and perceived barriers to its utilization. Design/Methods: A one-time survey was administered via the Canadian Paediatric Surveillance Program. The ten question adaptive survey was available in English or French, in either paper or electronic format. Survey responses were collected for 6 weeks in early 2020 with two reminders sent prior to survey closing. In addition to descriptive statistics, multinomial logistic regressions were built to examine pediatrician use of the IFHP, work with IFHP-covered patients, and provider characteristics associated with registration and use. Results: Of the 2, 753 pediatricians and pediatric subspecialists surveyed, there were 1006 respondents (36.5% response rate). 52.2% of respondents had provided care to the IFHP-eligible patients in the previous 6 months. Of those participants, only 26.4% were registered IFHP providers, and just 10% could identify all services covered by the IFHP (Figure 1). Knowledge of 80% or more of supplemental benefits was associated with registration status (adjusted odds ratio [aOR] 1.92; 95% CI 1.09 - 3.37). Amongst those who knew they were not registered, 70.2% indicated they did not know they had to register. aOR demonstrated that those with fewer years of practice had higher odds of not knowing that they had to register (aOR 1.22; 95% CI 1.01 - 1.49) Conclusion: We demonstrate that the IFHP is poorly utilized by pediatric providers, with low registration rates and poor understanding of the IFHP-covered supplemental services, even among those who have recently provided care to the IFHP-eligible patients. Efforts to improve registration and knowledge of the IFHP are essential to improving access to health care for refugee children and youth. Funding: Study funded by the CPSP Resident Research Grant